Explaining variation in the multiplicity of private social and environmental regulation: a multi-case integration across the coffee, forestry and textile sectors. (April 2014) - Turcotte, Marie-France; Reinecke, Juliane; den Hond, Frank
Abstract : Amid concerns for a regulatory void in transnational fields, the principle of private regulation has become institutionalized. Many sectors have seen the emergence of multiple and overlapping standards. When comparing the sectors, there is considerable variation in standard multiplicity. We build on three institutional perspectives that have been put forward to explain the emergence of sustainability standards – the economic, idealist and political-institutional perspectives – to analyze the phenomenon of standard multiplicity. Each perspective reflects a different kind of action logic and is simultaneously present and accessible to various parties involved. Based on a cross-sector analysis of standards multiplicity in the forestry, coffee and textile sectors, this article seeks to make two contributions. First, whereas these three perspectives have been presented as competing, we propose that they are complementary in offering partial explanations for different episodes in the dynamics underlying standards multiplicity in different sectors. Second, whereas most studies have analyzed standard setting in single sectors and thus have understood it as being an intra-sector phenomenon, our cross-sector analysis of the dynamics of standard setting suggests that it is propelled by both sector-specific contingencies and experiences as well as by the experiences from other sectors.